Assessing preservice secondary school mathematics teachers' knowledge of area - Thiam Yew, W.; Syed Zamri, S.N.A.; Hooi Lian, L.; Cheng Meng, C. (2013)
The purpose of this paper is to assess preservice secondary school mathematics teachers’ knowledge of area. Clinical interview technique was employed to collect the data. Subjects of this study consisted of eight preservice secondary school mathematics teachers enrolled in a Mathematics Teaching Methods course at a public university in Peninsula Malaysia. They were selected based on their majors (mathematics, biology, chemistry, physics) and minors (mathematics, biology, chemistry, physics). This paper presents the analysis of the responses of the subjects related to a particular task, namely notion of area. The finding suggests that five of the preservice teachers in this study had the correct notion of area that 2-dimensional shapes (closed plane shapes) and 3-dimensional shapes have an area. Different categories of incorrect notion of area were identified. Preservice teachers’ linguistic knowledge and ethical knowledge of area were discussed. The implication of this finding was also discussed.